Validation of a novel approach to identify potential radiologic predictors of myocardial infarction in patients under 50: a pilot study - Yu. A. Vasilev; Yu. F. Shumskaya; A. A. Ageev; L. V. Popova; E. A. Rogova; P. B. Gelezhe; A. N. Bariev; A. P. Goncha; D. V. Gatin; K. Yu. Bezhenova; N. A. Savin; R. V. Reshetnikov (Clinical Medicine (Russian Journal), 2026)
Cardiovascular diseases (CVDs) continue to be the leading cause of mortality in Russia. Over the past three decades, effective preventive measures have led to a one-third reduction in morbidity rates. However, there remains a significant risk of mortality among patients under 50 years of age who experience acute myocardial infarction (AMI). This highlights the need to identify additional predictors, including radiological features, to enhance prognostic models for CVD. There is an approach suggesting that incorporating low-correlation pairs of features may yield more informative model predictions. Aim. To evaluate the hypothesis that patients under 50 years of age with AMI exhibit distinct low-correlation pairs of characteristics, as identifi ed by chest computed tomography (CT), compared to patients over 50 years of age with AMI. Material and methods. This was a retrospective study involving patients who experienced their first AMI and had undergone chest CT 6–12 months prior to the cardiovascular event. Correlation matrices were created for patients under 50 years of age and those over 50. Subsequently, pairs of features with low correlation that were common to all patients were removed from the set of feature pairs for the younger group. Results. The study included 59 patients, with 12 under the age of 50 and 47 over 50. The groups diff ered in the prevalence of multivessel lesions, the presence of osteoporosis and hydrothorax as assessed by chest CT, and the average aortic size. By constructing correlation matrices and eliminating common feature pairs with weak correlations, we identified 12 unique feature pairs that could enhance existing risk models. Conclusion. Utilizing radiological markers to improve CVD prognosis shows promise, but further prospective cohort studies with larger sample sizes are necessary to validate these findings.